Drug resistance: a social perspective - Sawhney, Rajesh (Journal of Research in Biology, 2012)
Drug resistance is a defensive strategy developed by the microorganisms to evade the detrimental effects of antimicrobial agents. Over the years microorganisms have successfully counteracted the action of antimicrobials using both genetic methods such as random mutations, chromosomal or plasmid mediated transfer of genetic information and biochemical mechanisms like decreased permeability of the organism to the drug, inactivation of the inhibitor by enzyme produced by the resistant organism, modification of the properties of the drug receptor site, increased synthesis of an essential metabolite antagonistic for the drug. However, the human governed factors viz. faulty prescriptions, misdiagnosis, self medication, incomplete medication, reservation for antibiotic sensitivity tests, supplementation of antibiotics in cattle feed and toiletries seem to have taught and prompted the microorganisms, the so called miniature industries, to gear up to develop antibiotic resistant mechanisms. As a consequence, multi-drug resistant strains have posed a challenge to the humanity. The costly inputs and hardships of scientists in the laboratories unravel the mysteries and present a valuable product and technologies for human well being. However, the judicious use of the process, product or technology remains the joint responsibility of common masses, technocrats and the government. Thus, our roles to curb the factors that lead to drug resistance need to be given key priority. The approach could shun the burden of scientists and open new and well executed front to fight the nuisance of drug resistance.